2018
DOI: 10.1128/mbio.01166-18
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Assembly of the Bacillus anthracis Coat and Exosporium during Bacterial Spore Outer Layer Formation

Abstract: This work dramatically improves our understanding of the assembly of the outermost layer of the B. anthracis spore, the exosporium, a layer that encases spores from many bacterial species and likely plays important roles in the spore’s interactions with the environment, including host tissues. Nonetheless, the mechanisms directing exosporium assembly into a shell surrounding the spore are still very poorly understood. In this study, we clarify these mechanisms by the identification of a novel protein interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 50 publications
3
55
0
Order By: Relevance
“…Moreover, the absence of ExsY or CotY possibly affects the association of CotE with the released spores. Hence, since cotY spores possess a seemingly normal exosporium (7,9), our results suggest that CotE is needed during sporulation, only to guide cap localization and encasement by ExsY and CotY, but seems dispensable later for maintaining the integrity of the structure once assembled. Finally, while CotE completely encased exsY forespores, CotY assembly was blocked at the two-cap stage.…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, the absence of ExsY or CotY possibly affects the association of CotE with the released spores. Hence, since cotY spores possess a seemingly normal exosporium (7,9), our results suggest that CotE is needed during sporulation, only to guide cap localization and encasement by ExsY and CotY, but seems dispensable later for maintaining the integrity of the structure once assembled. Finally, while CotE completely encased exsY forespores, CotY assembly was blocked at the two-cap stage.…”
Section: Resultsmentioning
confidence: 83%
“…Sporulation is blocked at the late stage of engulfment in spoIIQ mutants of B. subtilis [11]. CotE plays an essential role in assembly of both the coat and exosporium in B. anthracis and B. cereus spores [13,21,41,42]. Thus, SpoIIB Bs may be able to stimulate sporulation of the B. anthracis pBspoIIB Bs /∆spoVG strain to the engulfment stage (Figure 7b).…”
Section: Discussionmentioning
confidence: 99%
“…CotO is conserved in Bacillus species that also have orthologs of CotY and CotZ. It was recently shown that cotO plays a related role in B. anthracis , where it is involved in the coordination of coat and exosporium assembly (Boone et al , ).…”
Section: Discussionmentioning
confidence: 99%